Discovering the anti-parasitic activity of melatonin loaded lecithin/chitosan nanoparticles against giardiasis and cryptosporidiosis in Balb/c infected mice - Mohamed Nasser; Mona B. Abd El-atif; Habiba Alaa; Mariam Abdelaziz; Mariam Mustafa; Mustafa Masour; Salma Magdy; Salma Mohsen; Yomna El Karamany; Alyaa Farid (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Giardia duodenalis and Cryptosporidium parvum are the primary causes of diarrhea with global attention due to the severe pathophysiological changes leading to mortality. During this study, we explored the biological protozoal contaminants (Giardia and Cryptosporidium spp.) in some areas of the Nile River. Then, we evaluated effectiveness of melatonin (Mel) and melatonin loaded lecithin/chitosan nanoparticles (Mel-LCNPs) against giardiasis and cryptosporidiosis in mice models using parasitological and inflammatory response examination. Results The number of positive samples for Cryptosporidium was higher than that for Giardia with percentage of 46.67% and 40.0%, respectively. Prior to treatment, the physical characterization (hydrodynamic size and zeta potential) and in vitro characterization of Mel-LCNPs were carried. Mel-LCNPs revealed a hydrodynamic size of 78.8 nm and a zeta potential of − 27.2 mV. Furthermore, they have powerful antioxidant and anti-inflammatory properties, while displaying minimal anticoagulant and cytotoxic effects during in vivo evaluation. Mel was consistently discharged from nanoparticles in a regulated and enduring manner for 36 h. Moreover, Mel in NPs has an entrapment efficiency (EE) of 33.6% and a drug loading capacity (DLC) of 7.2% and significant reduction (100% and 99.4%, respectively) in the shedding of Giardia cysts and Cryptosporidium oocysts. This reduction was higher than that observed with Mel alone or LCNPs alone on the 14th day post-infection. Moreover, mice of group V, which received Mel-LCNP treatment, exhibited significantly normal levels of interleukin-4 (IL-4) and interferon-gamma (IFN-γ) as well as healthy control mice group (group I). Conclusion Mel-LCNPs were highly effective preparations against giardiasis and cryptosporidiosis in Balb/c mice experimentally infected with proved antioxidant, anti-inflammatory, and immunological modulatory characteristics.